2018
DOI: 10.1007/s10570-018-1830-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional nanomaterials through esterification of cellulose: a review of chemistry and application

Abstract: As the most abundant biopolymer in nature, cellulose has become a fascinating building block for the design of functional nanomaterials. Owing to the presence of numerous hydroxyl groups, cellulose provides a unique platform for the preparation of new materials via versatile chemical modifications. This critical review aims to present the advances about nanomaterials based on cellulose derivatives with the focus on cellulose esters within the last two decades, including the chemistry and application of these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(120 citation statements)
references
References 199 publications
(184 reference statements)
1
118
0
1
Order By: Relevance
“…Therefore, short residence time is recommended to avoid extensive modification of cellulose fibers preserving their physicochemical properties as much as possible. On the other hand, targeting functional cellulose‐based materials with lactic acid (or other organic counterparts) could be an interesting approach [56] by using DES treatment with longer residence times. Nevertheless, data regarding the mechanical properties of those cellulose fibers are required to ascertain a successful application.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, short residence time is recommended to avoid extensive modification of cellulose fibers preserving their physicochemical properties as much as possible. On the other hand, targeting functional cellulose‐based materials with lactic acid (or other organic counterparts) could be an interesting approach [56] by using DES treatment with longer residence times. Nevertheless, data regarding the mechanical properties of those cellulose fibers are required to ascertain a successful application.…”
Section: Resultsmentioning
confidence: 99%
“…As pH increase to 6, the range broadened. The baseline CA membrane (M1) was negatively charged because it was made of cellulose acetate, of which the negative-charged acetyl group is the major functional group [51]. Then the pH value increased above 6, and the results showed that M1b presented a less negative surface charge as compared to M1, which might have been due to the presence of epoxide groups on polyGMA.…”
Section: Streaming Zeta Potentialmentioning
confidence: 99%
“…46 Several works demonstrated how reacting CNCs with carboxylic acid halides or anhydrides is possible to create ester linkages. 47 However, this approach usually does not allow for reactions in water suspension and it requires dispersion of CNCs into anhydrous and non-protic organic solvents such as acetonitrile, acetone or DMF. In 2015, Galkina et al investigated the esterification of NFC with 1,2,3,4-butanetetracarboxylic acid (BTCA), in the presence of sodium hypophosphite (SHP) acting as a base, followed by the attachment with TiO 2 ( Figure 5).…”
Section: Functionalization Through Chemical Modificationmentioning
confidence: 99%